Ceramic production in prehistoric northwest China: preliminary findings of new analyses of old material from the Museum of Far Eastern Antiquities, Stockholm - Hein, A; Stilborg, O (Elsevier, 2018)
The Neolithic painted pottery of northwest China has long been admired for its high level of craftsmanship. Yet, little is known about the technological processes and potting communities behind these objects. At the same time, the wide variety of supposedly less “beautiful” Bronze Age wares is often disregarded and simply ascribed to the emergence of multiple new cultures. In both cases, the relationship between object appearance, technology, and cultural expectations is unexplored. The present paper presents the first results of a pilot study using a combination of scientific techniques to learn about traditions of ceramic production and their transformation over time and space in prehistoric northwest China. The basis of this study are finds excavated in the 1920s and held in the Museum of Far Eastern Antiquities in Stockholm. This collection has long lain dormant and their potential remains largely unexplored. This paper draws attention to the collection and at the same time shows the usefulness of combining thin-section petrography and portable X-ray fluorescence for this specific set of material and research questions. This analysis of a small sample already provides important insights. For instance, it shows continuity in criteria of raw material selection during the Neolithic but a radical break in tempering behavior at the transition from early to late Bronze Age. The study also identifies technical challenges as well as possibilities posed by the quality of the local raw material in conjunction with long-standing traditions of high-level local craftsmanship. All of these phenomena, so the paper shows, are best investigated with a combination of petrographic and chemical analyses on archaeological and geological samples viewed in a comparative perspective.